The Role Of Creative Value Relationships "Teacher-Pupil" In The Development Of Students' Creative Skills - Nasriev Bakhtiyor Kakhramonovich; Olympus Temur Khasanovich (Genius Journals, 2023)
This article discusses the importance of developing the creative abilities of students based on interactive teaching methods and technologies. Works of a number of scientists about creativity. Opinions are presented on the assessment and development of practical skills and creative abilities of students using international experience.
Keywords: Creativity; abilities; preschool educational organizations